PROTON PUMP INHIBITORS AND THE RISK OF CHRONIC KIDNEY DISEASES: A CRITICAL REVIEW - J., SHAREEF; S. B., SRIDHAR; A., SHARIFF (International Journal of Current Pharmaceutical Research, 2020)
Proton pump inhibitors (PPIs) are most widely used medications for acid related gastrointestinal disorders. Accessible evidence based studies suggest that the increased use of PPI is linked to a greater risk of developing kidney diseases. This review aims to determine the association of kidney disease with the use of proton pump inhibitor with various study designs. PubMed, Scopus and Google Scholar databases as well as a reference list of relevant articles were systematically searched for studies by using the following search terms; ‘proton pump inhibitors’, ‘acute kidney injury’, ‘chronic kidney disease’ and ‘end stage renal disease’. Both observational and randomized controlled trials (RCTs) exploring the association of PPI use with kidney disease were eligible for inclusion. A total of 8 articles, including 9 studies (n = 794,349 participants) were identified and included in the review. Majority of the studies showed a higher risk of kidney outcomes in patients taking PPIs, with effect higher of acute kidney injury (4-to 6-fold) compared with chronic kidney disease and end stage renal disease (1.5-to 2.5-fold). However, the studies suggest that the strength of evidence is weak and could not prove causation. The risk increased considerably with the use of high dose of PPIs and prolonged duration of exposure necessitates the monitoring of renal function. Exercising vigilance in PPI use and cessation of proton pump inhibitor when there is no clear indication may be a reasonable approach to reduce the population burden of kidney diseases.